Giant Hepatic Hemangioma and Placental Chorangiosis: A Unique Case of Stillbirth?. (4th March 2019) - Paudice, Michele; Peñuela, Leonardo Alett; Torielli, Flaminia; Spina, Bruno; Remorgida, Valentino; Buffelli, Francesca; Fulcheri, Ezio; Arioni, Cesare; Vellone, Valerio Gaetano
Abstract: Introduction: Hepatic hemangiomas (HH) are benign vascular tumors, and when large, may contribute to fetal morbidity/mortality. Chorangiosis is placental villus capillary hypervascularity, probably linked with fetal hypoxia. Case report: We present a macrosomic stillbirth at 39 + 3 weeks of gestation with congestive heart failure (CHF) and myocardial infarction. A giant right hepatic lobe HH was present, along with placental chorangiosis. Conclusion: A common pathogenetic pathway between congenital HH and placental chorangiosis has not been reported. Our case suggests that the effects of HH and chorangiosis increase the risk of late fetal loss due to the high-output CHF.